Depiction of Brahma, Shiva and Vishnu - Temples of India Project Team (Jio Institute, 2024)
Brahma (right), Shiva (center), Vishnu (left), shikhara, garbhagriha, Mahakal Temple, Bijolia, Bhilwara, Rajasthan, 11th-13th century CE.